Comprehensive analysis of clinical Burkholderia pseudomallei isolates demonstrates conservation of unique lipid A structure and TLR4-dependent innate immune activation - Sengyee, S; Yoon, S; Paksanont, S; Yimthin, T; Wuthiekanun, V; Limmathurotsakul, D; West, T; Ernst, R; Chantratita, N (Public Library of Science, 2018)
Burkholderia pseudomallei is an environmental bacterium that causes melioidosis, a major community-acquired infection in tropical regions. Melioidosis presents with a range of clinical symptoms, is often characterized by a robust inflammatory response, may relapse after treatment, and results in high mortality rates. Lipopolysaccharide (LPS) of B. pseudomallei is a potent immunostimulatory molecule comprised of lipid A, core, and O-polysaccharide (OPS) components. Four B. pseudomallei LPS types have been described based on SDS-PAGE patterns that represent the difference of OPS-type A, type B, type B2 and rough LPS. The majority of B. pseudomallei isolates are type A. We used matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) followed by electrospray ionization quadrupole time-of-flight mass spectrometry (ESI-QqTOF MS) and gas chromatography to characterize the lipid A of B. pseudomallei within LPS type A isolates. We determined that B. pseudomallei lipid A is represented by penta- and tetra-acylated species modified with 4-amino-4-deoxy-arabinose (Ara4N). The MALDI-TOF profiles from 171 clinical B. pseudomallei isolates, including 68 paired primary and relapse isolates and 35 within-host isolates were similar. We did not observe lipid A structural changes when the bacteria were cultured in different growth conditions. Dose-dependent NF-κB activation in HEK cells expressing TLR4 was observed using multiple heat-killed B. pseudomallei isolates and corresponding purified LPS. We demonstrated that TLR4-dependent NF-κB activation induced by heat-killed bacteria or LPS prepared from OPS deficient mutant was significantly greater than those induced by wild type B. pseudomallei. These findings suggest that the structure of B. pseudomallei lipid A is highly conserved in a wide variety of clinical and environmental circumstances but that the presence of OPS may modulate LPS-driven innate immune responses in melioidosis.